Sperm Utilize Tumor Necrosis Factor Alpha to Shut Down a 2-Methoxyestradiol Nongenomic Pathway That Accelerates Oviductal Egg Transport in the Rat - Cardenas-Sankan, G; Orihuela-Diaz, P; Reuquen-Lopez, P; Orostica, M (BioScientifica Ltd., 2023)
The transport of oocytes or embryos throughout the oviduct to the implantation site in the uterus is defined as egg transport. In the rat, 2-methoxyestradiol (2ME) accelerates egg transport through the oviduct via a nongenomic pathway. Mating is known to shut down this 2ME pathway and then trigger an estradiol genomic pathway that accelerates egg transport. Here, we tested whether intrauterine insemination (IUI) or vaginocervical stimulation (VCS) shuts down the 2ME nongenomic pathway that accelerates egg transport, and if these mating components require tumor necrosis factor alpha (TNF-α). Levels of TNF-α and the mRNA for TNF-α receptors were measured in the oviduct of IUI or VCS rats. The tissue distribution of TNF-α receptor proteins and the concentration of the mRNA for catechol-O-methyl transferase (Comt) and 2ME were also analyzed in the oviduct. Finally, we assessed whether 2ME accelerates egg transport in IUI or VCS rats previously treated with the TNF-α antagonist W9P9QY. Results show that IUI, but not VCS, increased TNF-α and their receptors in the oviduct. IUI and VCS did not change the tissue distribution of TNF-α receptors; however, both decreased the oviductal concentration of Comt and 2ME. IUI and VCS each blocked the 2ME-induced egg transport acceleration; however, only the IUI was antagonized by the TNF-α antagonist. We concluded that IUI and VCS inhibit the 2ME nongenomic pathway that accelerates egg transport; however, the vias of action are distinct, with a TNF-α increase on spermatozoa presence being required for the shutdown of the 2ME pathway. © 2023 Society for Reproduction and Fertility.